Advances in personal construct psychology. (Greenwich, Conn. Jai Press, 1990)
Biennial
Keywords: Personal construct theory -- Periodicals; Personality -- Periodicals; Psychological Theory -- Periodicals; Psychotherapy -- Periodicals